Increased neural activity during high working memory load predicts low relapse risk in alcohol dependence. (22nd October 2013) - Charlet, Katrin; Beck, Anne; Jorde, Anne; Wimmer, Lioba; Vollstädt‐Klein, Sabine; Gallinat, Jürgen; Walter, Henrik; Kiefer, Falk; Heinz, Andreas
Abstract Working memory (WM) impairments are often observed in alcohol‐dependent individuals, especially in early abstinence, which may contribute to an increased relapse risk after detoxification. Brain imaging studies on visuospatial WM in alcohol‐dependent patients compared to controls indicate that information processing requires compensatory increased neural activation to perform at a normal level. However, to date, no study tested whether such increased neural WM activation patterns or the lack thereof predict relapse behavior in alcohol‐dependent individuals, and whether such differences persist when adequately correcting for individual grey matter differences. We combined analyses of neural activation during an n‐back task and local grey matter volumes using Biological Parametric Mapping in 40 detoxified alcohol‐dependent patients and 40 matched healthy controls (HC), and assessed prospective relapse risk during a 7‐month follow‐up period. Despite equal task performance, we found increased functional activation during high versus low cognitive WM load (2‐back–0‐back) in bilateral rostral prefrontal cortex (BA10) and bilateral ventrolateral prefrontal cortex (BA45, 47) in prospective abstainers versus relapsers, and further in left/right lateral/medial premotor cortex (BA6, 8) in abstainers versus HC. In prospective abstainers, but not relapsers, subtle cognitive impairment was associated with increased neural task activity in the premotor cortex. These findings suggest that in prospective abstainers, higher functional engagement of presumably less impaired neural resources in executive behavioral control brain areas (BA10, 45, 47, 6, 8) may constitute a resilience factor associated with good treatment outcome.